Evaluation on the knowledge, attitude, and practices toward evidencebased practice in computed tomography among radiographers / Nur Ezzatie Aqillah Mohd Sauti, Lyana Shahirah Mohamad Yamin - Nur Ezzatie Aqillah, Mohd Sauti; Lyana Shahirah, Mohamad Yamin (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
The study aims to identify the level of knowledge, attitude, and practices toward evidence-based practice (EBP) in computed tomography (CT) among radiographers and factors that influence the use of EBP in CT among the radiographers. This is a cross-sectional study to evaluate the knowledge, attitude, and practice toward evidence-based practice in computed tomography among radiographers. The research was done by using a self-administered questionnaire covering socio-demographic features, knowledge on EBP, understanding of specific terms related to EBP, access and availability toward literature, attitudes and practices, and also barriers perceived toward EBP in CT that had been distributed to 30 radiographers in Hospital Muar. All the data obtained were analyzed using SPSS software version 21. The level of knowledge toward EBP in CT among radiographers was high, where 63.3% of the respondents had high knowledge, and only 36.7% of the respondents had a low level of knowledge toward EBP in CT. The radiographer also had a high level of attitude and practices by 56.7%, and 43.3% of the respondents had a low level of attitude and practices toward EBP in CT. The barriers that affect the implementation of EBP among radiographers involve in CT was the inability to critically appraise literature. The lack of information resources and insufficient time also become the most factors that influence the use of EBP in CT. In conclusion, from the findings, most of the radiographers had high a level of knowledge, attitude, and practices toward evidence-based practice in CT and understood most of the specific terms related to EBP.